Service Quality, Tourist Satisfaction, And Loyalty In Sustainable Nature Tourism Supporting The Sdgs In Jayawijaya, Highland Papua - Tiomy B Adi; Ayu Anggraini Tambunan; Erick Karunia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This study aims to analyse the influence of service quality, tourist satisfaction, tourist loyalty, and the role of local communities on the achievement of the Sustainable Development Goals (SDGs) within the natural tourism sector in Jayawijaya Regency. Regional tourism development should not merely focus on increasing visitor numbers but must also ensure its contribution to sustainable development. encompassing economic, social, and environmental dimensions. This research employed a quantitative approach using a survey method involving 250 tourists who had visited natural tourism destinations in Jayawijaya. The data were analysed using multiple linear regression to examine the effect of each independent variable on the achievement of the SDGs. The findings reveal that service quality, tourist satisfaction, tourist loyalty, and the role of local communities have a positive and significant influence on the achievement of the SDGs. Among these variables, the role of local communities emerges as the most dominant factor in supporting sustainable tourism development. These findings highlight the importance of improving destination management quality, enhancing tourist experiences, fostering visitor loyalty, and empowering local communities in order to realise sustainable tourism. This study contributes theoretically to the development of sustainable tourism models and offers practical implications for regional policymakers and stakeholders in formulating policies aligned with the SDGs agenda.